Hope and psychological well-being after 5 years become breast cancer survivors: a Qualitative Study - Yesiana Dwi Wahyu Werdani; Arief Widya Prasetya (Alma Ata University Press, 2022)
Background: Cancer is perceived as a deadly disease for most people, it will affect the hope and psychological well-being of long-term cancer survivors. Objectives: This study aimed to explore changes in hope and psychological well-being after 5 years become breast cancer survivors. Methods: This was a qualitative study with a phenomenological design. Samples were 23 breast cancer survivors in three health centers in Surabaya Indonesia taken by purposive sampling technique based on inclusion criteria. An in-depth interview was done when collecting the data. The interview was recorded with the permission of the participants. The data were inductively analyzed through conventional content analysis. Results: The participant has an age range of 41 – 70 years old, and most of them are no longer working since being diagnosed with cancer. This study found 4 themes consisting of the first theme was positive hope about cancer with 3 sub-themes: hope to recover, hope no recurrence occurs, and hope to be healthier, the second theme was a good future with 3 sub-themes: long life, back to work, and optimism, the third theme was positive psychological well-being with 3 sub-themes: positive thinking, self-control ability, happy feeling, the last theme was a close relationship with God with 2 sub-themes: grateful and pray, repentance. Conclusions: Breast cancer survivors who have been diagnosed for more than 5 years and have completed cancer therapy had a positive hope to recover, are optimistic about the future and are closer to God, this encourages the achievement of positive psychological well-being.